Frequency of HBsAg variants in occult hepatitis B virus infected patients and detection by ARCHITECT HBsAg quantitative - He, Chengshan; Liu, Yang; Jiang, Xiudi; Xu, Zheng; Xiang, Zhouhong; Lu, Zhicheng (Frontiers in Cellular and Infection Microbiology, 2024)
To analyze the amino acid substitution caused by mutations in the major hydrophilic region (MHR) of the S-region genes in the serum samples of occult hepatitis B virus infection (OBI), and to explore the reasons for the missed detection of HBsAg. Method: The full-length gene of the S-region in hepatitis B virus(HBV) in the chronic hepatitis B virus(CHB)(10 samples) and OBI groups(42 samples) was amplified using a lab-developed, two-round PCR amplification technology.The PCR amplification products were sequenced/clone sequenced, and the nucleotide sequences of the S-region gene in HBV were compared to the respective genotype consensus sequence.Results: Only 20 of the 42 samples in the OBI group had the S-region genes successfully amplified, with the lowest HBV DNA load of 20.1IU/ml. As S-region genes in HBV, 68 cloned strains were sequenced.In the OBI and CHB groups MHR region, with a mutation rate of 3.21% (155/4828) and 0.7% (5/710). The genetic mutation ratewas significantly higher in the OBI group than in the CHB group (P<0.05). The common mutation types in the MHR region were: I126T, L162R, K122E, C124R, and C147Y.Mutations at s122, s126, and s162 were associated with subgenotypes, most of which being C genotypes. The high-frequency mutation sites L162R and K122E found in this study have not been reported in previous literature.The results of this study confirmed that MHR mutations can cause the missed detection of HBsAg, giving rise to OBI.